The brother of Jesus : the dramatic story & meaning of the first archaeological link to Jesus & his family - Shanks, Hershel; Witherington, Ben, III, 1951- (San Francisco : HarperSanFrancisco, 2003)
The discovery of a limestone burial box with the inscription, "James, son of Joseph, brother of Jesus" set the world of biblical archaeology abuzz. Hershel Shanks and Ben Witherington III reveal not only what the discovery means for understanding the Bible, but also what it shows about the family of Jesus and the earliest Christians.
Introduction / Hershel Shanks -- Foreword / g mazing discovery --g
Includes bibliographical references.
Keywords: James, -- Brother of the Lord, Saint; Christianity -- Origin